Effects of Mesophyll Conductance and Nitrogen Content on Carbon Assimilation During Low-Water Stress in Leaf Lettuce Cultivars - Renée L. Eriksen; Pawan Kumar; Germán Sandoya; Neil Adhikari; Beiquan Mou (Horticulturae)
Plants have evolved many mechanisms to acclimate to deficit soil moisture conditions, and breeders can use these mechanisms to develop crops with improved abiotic stress tolerance in irrigated agriculture. However, many of these mechanisms are not compatible with crops for which leafy biomass is the primary agricultural product, such as lettuce. Improving biomass production in lettuce under conditions that induce stomatal closure involves understanding traits that compensate for stomatal limitations during photosynthesis. We tested the hypothesis that cultivars with tolerance to stomatal limitations during low-water stress have higher carbon assimilation, which might result from higher mesophyll conductance or higher total nitrogen content. We found higher carbon assimilation in the tolerant cv. Slobolt and higher mesophyll conductance and nitrogen content in the tolerant cv. Australian. We sequenced the transcriptomes, and found an increased expression of transcripts involved in carbon assimilation during stomatal limitations in tolerant cultivars, including a carbonic anhydrase that may be involved in mesophyll conductance. We propose that breeding for improved and consistent biomass production in lettuce should focus on stacking traits of small effect, including improved nitrogen uptake and mesophyll conductance.